2018
DOI: 10.1002/ijop.12518
|View full text |Cite
|
Sign up to set email alerts
|

Environmental attitudes in China: The roles of the Dark Triad, future orientation and place attachment

Abstract: Given the current environmental situation and social change in China, we explored the relationships between the Dark Triad traits (Machiavellianism, narcissism and psychopathy) and environmental attitudes (beliefs regarding environmentally related issues), and the mediating roles of future orientation (the tendency to plan for meeting long-term objectives) and place attachment (the emotional connection with the place of residence) in these relationships. Using a national sample from all 31 provinces of mainlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…However, in other countries, the results may differ. Specific social issues and serious environmental problems in China’s current development may affect the entrepreneurial attitude of potential entrepreneurs to a certain extent (Huang et al, 2018). Therefore, future research should consider collecting data from different countries in order to understand the differences in the impact of individual personality traits on SEO (Chang and Park, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in other countries, the results may differ. Specific social issues and serious environmental problems in China’s current development may affect the entrepreneurial attitude of potential entrepreneurs to a certain extent (Huang et al, 2018). Therefore, future research should consider collecting data from different countries in order to understand the differences in the impact of individual personality traits on SEO (Chang and Park, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, environmental problems are understood as social dilemmas with time conflicts, representing tensions between the satisfaction of short- and long-term interests (Milfont et al, 2012). For example, Huang et al (2018) showed that the dark triad was negatively correlated with environmental attitudes and suggested that when individuals with the dark triad weigh short-term interests and future environmental interests, they tend to satisfy their short-term interests at the expense of future environmental interests, which is ultimately expressed as negative environmental attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been discussed (but not yet examined) that everyday sadism is negatively associated with attitudes toward the environment ( Mertens et al, 2021 ). Taken together, the dark tetrad and PEB should be negatively related due to this socially aversive nature ( Paulhus and Williams, 2002 ; Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…More specifically, the definition of Machiavellianism is based on the 16th-century philosopher Nicolo Machiavelli and describes people who are “cynical, unprincipled, believe in interpersonal manipulation as the key for life success, and behave accordingly” ( Furnham et al, 2013 , p. 201). Recent results showed a negative association of Machiavellianism and psychopathy with environmental attitudes ( Huang et al, 2019 ). In addition, Machiavellianism predicted the justification of eating meat ( Mertens et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%